THE COMPARISON OF THE LEVEL OF EXPOSURE TO THE SKIN SURFACE TEMPERATURE AND WORKER FATIGUE IN THE METAL CASTING INDUSTRY INDUCTION KITCHEN SYSTEM; USING ONE-OPERATOR LADLE-KOWI AND TWO-OPERATOR LADLE-KOWI - wahyu SUSIHONO; Wahyu wahyu Susihono (Journal of Global Pharma Technology, 2017)
Ladle-kowi is a liquid steel of tool transportation coming from the induction industry. There are two designs of Ladle-kowi such as; Ladle-kowi designed to be operated by one-operator weighing at 15 kg and Ladle-kowi operated by two-operator weighing at 50 kg. Diverse design drafts of Ladle-kowi affect the differences in physical and mental burdens received by every worker. Up to now, the use Ladle-kowi in the metal casting industry of induction system has become a necessity that functioned as a tool for the transport and distribution of liquid steel into the molds. Problems faced by many workers are on the selection of ladle-kowi which will affect the physiological condition of the human body in the form of exposure and fatigue on peripheral skin surface temperature. Human nature has the ability, skill and limitations of laboring which has not been used as a parameter for determining comfortable and safe working conditions. This study aims to determine the level of exposure of the skin surface temperature and the level of fatigue which is then used as the basis of proposals to improve working conditions and serve as the basis of recommendations for a more convenient and safe Ladle-kowi usage. The subjects in this study was workers in the metal casting industry using the facility in the form of Ladle-kowi with one-operator with a capacity of 15 kg filled with molten steel and Two-operator Ladle-Kowi filled with liquid steel capacity of 50 kg. This study belongs to the category of taxonomic research in the form of cross sectional analytic. Subjectsw were randomly selected from all workers in the metal casting industry of induction system. Samples taken were 14 people who have been taken and met the criteria for inclusion and exclusion. The results showed that exposure to the skin surface temperature is lower (0,03OC) than when workers used one-operator ladle-kowi compared with workers using two-operator ladle-kowi. There is a strong positive correlation patterns of exposure time to the degree of exposure to the skin surface temperature. The mean score of fatigue in general when using one-operator ladle-kowi is 97.25 ± 10.75 consisting of activities fatigue by 32.67 ± 4.78, motivational fatigue by 33.50 ± 5.58, and physical fatigue by 31.08 ± 6, 10, while the mean score of fatigue in general when using two-operator ladle-kowi reached 93.58 ± 10.25  consisting of activities fatigue by 29.33 ± 2.00, motivational fatigue by 31.83 ± 6.14, and physical fatigue by 32,42 ± 5.35. Only in aspects of activities fatigue, they experienced the highest fatigue differences of 10.20% (p <0.05) using one-operator ladle-kowi than to using the two-operator ladle-kowi. Conclusion: The use of one-operator ladle-kowi is better when compared with the use two-operator ladle-kowi, seen from the level of exposure of the surface temperature of the skin, but two-operator ladle-kowi is better when compared to using a one-operator ladle-kowi, seen from the average value of general fatigue (down 3.77%). One-operator ladle-kowi needed improvements in the form of a  working re-organization so that workers' fatigue can be lowered, while the to operators ladle-kowi required the addition of a shield mounted on a frame ladle-kowi to reduce the radiated heat of molten steel